Pengaruh Kepemimpinan Transformasional, Budaya Organisasi, dan Employee Engagement terhadap Kinerja Karyawan melalui Organizational Trust sebagai Variabel Intervening - Zubastian Rachman; Siti Mujanah; Ida Aju Brahma Ratih (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the effects of transformational leadership, organizational culture, and employee engagement on employee performance, both directly and indirectly through organizational trust as an intervening variable. The research was conducted at PT Kilau Wijaya Dana Dentika, a dental healthcare provider operating five clinics in Jakarta, Tangerang, Karawang, and Bekasi. This explanatory quantitative study involved all 71 employees using a census sampling technique. Data were collected through a five-point Likert-scale questionnaire and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings indicate that transformational leadership, organizational culture, and employee engagement significantly influence organizational trust. However, only organizational culture and organizational trust have significant direct effects on employee performance. Transformational leadership and employee engagement do not directly affect performance but have significant indirect effects through organizational trust, demonstrating its mediating role. The model explains 61.2% of the variance in organizational trust and 68.5% of the variance in employee performance. These findings support Social Exchange Theory by highlighting organizational trust as a key psychological mechanism linking leadership, organizational culture, and employee engagement to improved employee performance in the dental healthcare service sector.